The impact of the strategy of laser treatment on structure formation of steel in a state of pre-transformation; Междисциплинарные проблемы аддитивных технологий - Gvozdev A. E.; Minayev I. V.; Tikhonova I. V.; Sergeyev A. N.; Chukanov A. N.; Khonelidze D. M.; Maliy D. V. (2017, 2017)
Заглавие с титульного экрана